A new adduct of iriflophene and flavonoid from Sedum aizoon L. (October 2020) - Xiong, Yan; Yi, Ping; Du, Caixia; Zhang, Jiayu; Yuan, Chunmao; Huang, Liejun; Hao, Xiaojiang; Gu, Wei
Abstract: A new adduct of iriflophene and flavonoid, 1, 8, 10, 10b-tetrahydroxy-3-methoxy-5a-(3, 4-dihydr- oxyphenyl)-9-(4-hydroxybenzoyl)-5a, 10b-dihydro-11 H -benzofuro[2, 3-b]chromen-11-one (1 ), together with six known compounds were isolated from the EtOH extract from Sedum aizoon L. Their chemical structures were elucidated by analyses of spectral data. The chemotaxonomic analysis of the compounds was discussed, compounds 1 –4 provide important chemotaxonomic markers for S . aizoon . Highlights: A phytochemical investigation of the aerial parts of Sedum aizoon has been carried out. A new adduct of iriflophene and flavonoid, compound 1 was isolated from S. aizoon . Compounds 5 and 7 were reported from the genus Sedum for the first time. The chemotaxonomic significance of the isolated compounds were summarized.